2022
DOI: 10.3390/cancers14215374
|View full text |Cite
|
Sign up to set email alerts
|

The Proliferative Role of Immune Checkpoints in Tumors: Double Regulation

Abstract: Cancer remains a serious social health problem, and immunotherapy has become the major treatments in tumor treatment. Additionally, improving the efficiency and safety of treatment is necessary. Further, more therapy targets are warranted for future tumor treatments. In this review, in addition to examining the currently recognized role of immune regulation, we focus on the proliferative role of 15 immune checkpoints in various tumors, including PD1, PD-L1, FGL1, CD155, CD47, SIRPα, CD276, IDO1, SIGLEC-15, TIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…We believe that Gal-9’s ability to counteract tumor cell evasion from immune surveillance may be influenced by tumor heterogeneity and its varying benefits for immunotherapy. Interestingly, studies on “unlimited proliferation” and “apoptosis”, also tumor hallmarks, have found that these two “hallmarks” are concentrated in gastrointestinal tumors ( Tang et al, 2022 ), including colorectal cancers ( Sasidharan Nair et al, 2018 ; Blair et al, 2021 ), EAC ( Akashi et al, 2017 ), ESCC ( Chiyo et al, 2019 ), gallbladder ( Tadokoro et al, 2016 ), and bile duct ( Kobayashi et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that Gal-9’s ability to counteract tumor cell evasion from immune surveillance may be influenced by tumor heterogeneity and its varying benefits for immunotherapy. Interestingly, studies on “unlimited proliferation” and “apoptosis”, also tumor hallmarks, have found that these two “hallmarks” are concentrated in gastrointestinal tumors ( Tang et al, 2022 ), including colorectal cancers ( Sasidharan Nair et al, 2018 ; Blair et al, 2021 ), EAC ( Akashi et al, 2017 ), ESCC ( Chiyo et al, 2019 ), gallbladder ( Tadokoro et al, 2016 ), and bile duct ( Kobayashi et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…These show that the CD27 has a dual role in the progression of certain cancers 42 . The study of Ortiz-Cuaran et al demonstrated that CD27L is highly expressed in non-small cell lung cancer and predicts reduced infiltration of CD8 + T cells as well as immune depletion 43 , 44 . At the same time, CAR-T therapy targeting CD27L has also become a new role in cancer treatment 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary inquiries have revealed the presence of specific immunosuppressive metabolites expressed on effector T cells, which function to inhibit excessive activation of T cells and the resulting emergence of autoimmune conditions. As a result, widespread attention has been attracted to the role of these molecules in regulating immune balance ( Tang et al, 2022b ). Additional examination has revealed more information regarding the increased presence of these checkpoint molecules in circumstances like cancerous growths, persistent viral infections, and bacterial infections within immune cells.…”
Section: Immune Checkpointsmentioning
confidence: 99%